FITRAH SEBAGAI POTENSI ANAK DIDIK DALAM PROSES PEMBELAJARAN - Mukhtar Nuhung (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
This article tries to outline the basic potential of a student from birth who needs efforts to develop it into factual and actual. In the view of Islam, the basic potential possessed by humans is called fitrah, which is equipped with human resources, even though everything is still dependent on the process of further development through education. With the education process, humans are able to shape their personalities, transfer their culture from one community to another, know good and bad values, and so on. Education is the process of developing the nature of students to be actual so as to form a moral Muslim personality (akhlakul karimah). Thus it is clear that Islam recognizes the role of basic factors and teaches in children's development. Based on the conceptualization, Islamic education is expected to function as a meaning to develop the potential of students in accordance with their nature.>This article tries to outline the basic potential of a student from birth who needs efforts to develop it into factual and actual. In the view of Islam, the basic potential possessed by humans is called fitrah, which is equipped with human resources, even though everything is still dependent on the process of further development through education. With the education process, humans are able to shape their personalities, transfer their culture from one community to another, know good and bad values, and so on. Education is the process of developing the nature of students to be actual so as to form a moral Muslim personality (akhlakul karimah). Thus it is clear that Islam recognizes the role of basic factors and teaches in children's development. Based on the conceptualization, Islamic education is expected to function as a meaning to develop the potential of students in accordance with their nature.